2020
DOI: 10.1155/2020/6950530
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Slovenian Adults in Community-Based Whole-Food Plant-Based Lifestyle Program

Abstract: Objective. Adopting a plant-based diet (PBD) and lifestyle is healthy, sustainable, and increasingly popular, while also demanding. Individuals might face challenges to maintain this lifestyle. We aimed to determine the anthropometric values and lifestyle factors and motives of adults to adopt a whole-food, plant-based (WFPB) lifestyle by joining our ongoing, community-based, WFPB lifestyle program 0.5–10 years ago. Methods. We measured body mass index (BMI) and body fat percentage status (BF%) using bioimpeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…The decision to go on a healthy vegan or healthy non-vegan diet may have a number of underlying motives, and usually the strongest motives are primarily related to health reasons. Furthermore, researchers have found several common motives for choosing a vegan diet, from ethical and health benefits, BM management/appearance, eating to satiety, environmental concerns, and religious reasons [ 56 , 64 , 65 , 66 ]. On the other hand, the Finnish study suggested that eating motives are also associated with changes in diets, meaning that some eating motives might be being positively related to dietary change towards a vegan diet, whereas other motives could be interpreted as barriers to change (i.e., convenience and price motives) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to go on a healthy vegan or healthy non-vegan diet may have a number of underlying motives, and usually the strongest motives are primarily related to health reasons. Furthermore, researchers have found several common motives for choosing a vegan diet, from ethical and health benefits, BM management/appearance, eating to satiety, environmental concerns, and religious reasons [ 56 , 64 , 65 , 66 ]. On the other hand, the Finnish study suggested that eating motives are also associated with changes in diets, meaning that some eating motives might be being positively related to dietary change towards a vegan diet, whereas other motives could be interpreted as barriers to change (i.e., convenience and price motives) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total score range was from 0 to 21, where a higher score indicated worse sleep quality and >5 indicated poor sleep quality [ 55 ]. These lifestyle characteristics questionnaires had previously been used in the adult Slovenian population [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results suggested that a vegan diet supplemented with vitamins B 12 and D, EPA/DHA, creatine and vegan protein combined with a resistance workout may support the loss of body mass and BF % but preserve and even increase muscle mass [147]. Furthermore, for physically active people and athletes, there is room for further appropriate supplementation of a conventional vegan diet according to individuals' health status, needs and goals without compromising their health (e.g., until proven otherwise), through the use of plant-based protein supplements or meal replacements, sport drinks and creatine [16,140,148,149].…”
Section: Sport and Exercise Performancementioning
confidence: 99%
“…Regardless, different motives can lead to the adoption of a vegan diet. According to several studies, common motives for choosing a vegan diet include ethical and health-related benefits, body mass management, environmental concerns and religious reasons [12][13][14][15][16][17][18]. With that in mind, this has led to the development of new vegan products for the consumer market, including meat alternatives, other vegan alternatives [17] and plant-based protein supplements [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The external load of 10 kg constituted approximately 13% of body weight (BW) for men and 18% for women, whereas the percentage values for men and women doubled respectively for the external load of 20 kg. Additionally, the inclusion criteria included only participants with moderate physical activity level, according to the International Physical Activity Questionnaire (long form) [35,36]. Moreover, only individuals with no history of knee disorder or other diagnosed injury or pathology within the lower extremity were included in the study group.…”
Section: Participantsmentioning
confidence: 99%